Liquidity, initial public offering (ipo) long-term return and government ownership: Evidence from bursa malaysia ipo stocks - Ramlee, Roslily; Ali, Ruhani (Universiti Sains Malaysia, 2012)
Prior studies testing the relationship between initial public offering (IPO) returns and liquidity are mostly for the developed markets. The disperse ownership in the corporation and more well informed investors in the developed markets support their findings. On the other hand, the nature and behaviour of emerging stock markets such as Malaysia differ from the developed markets. The concentrated ownership in the corporations partly due to government ownership to a certain extent could provide different views on the relationship between liquidity and return. Using 283 samples of IPO stocks listed on Main Board and Second Board of Bursa Malaysia from 1998 to 2008, the study examines the relationship between liquidity and IPO long-term return and the moderating effect of government shareholdings on the relationship between the two variables. The results showed one proxy of liquidity that is average monthly turnover as able to explain the market-adjusted long-term return of IPO stocks when equally weighted returns are calculated. Further, the government shareholdings in the IPO stocks positively moderate the relation between liquidity and long-term return.